Systematic Review of Mental Health Problems and Violent Extremism. Issue 1 (2nd January 2021) - Gill, Paul; Clemmow, Caitlin; Hetzel, Florian; Rottweiler, Bettina; Salman, Nadine; Van Der Vegt, Isabelle; Marchment, Zoe; Schumann, Sandy; Zolghadriha, Sanaz; Schulten, Norah; Taylor, Helen; Corner, Emily
ABSTRACT: This systematic review assesses the impact of mental health problems upon attitudes, intentions and behaviours in the context of radicalisation and terrorism. We identified 25 studies that measured rates of mental health problems across 28 samples. The prevalence rates are heterogenous and range from 0% to 57%. If we pool the results of those samples (n = 19) purely focused upon confirmed diagnoses where sample sizes are known (n = 1705 subjects), the results suggest arate of 14.4% with aconfirmed diagnosis. Where studies relied upon wholly, or in some form, upon privileged access to police or judicial data, diagnoses occurred 16.96% of the time (n = 283 subjects). Where studies were purely focused upon open sources (n = 1089 subjects), diagnoses were present 9.82% of the time. We then explore (a) the types and rates of mental health disorders identified (b) comparison/control group studies (c) studies that explore causal roles of mental health problems and (d) other complex needs.